Influence of room heating on ambulatory blood pressure in winter: a randomised controlled study. Issue 6 (27th February 2013) - Saeki, Keigo; Obayashi, Kenji; Iwamoto, Junko; Tanaka, Yuu; Tanaka, Noriyuki; Takata, Shota; Kubo, Hiroko; Okamoto, Nozomi; Tomioka, Kimiko; Nezu, Satoko; Kurumatani, Norio
Abstract : Background: Previous studies have proposed that higher blood pressure (BP) in winter is an important cause of increased mortality from cardiovascular disease during the winter. Some observational and physiological studies have shown that cold exposure increases BP, but evidence from a randomised controlled study assessing the effectiveness of intensive room heating for lowering BP was lacking. Objectives: The present study aimed to determine whether intensive room heating in winter decreases ambulatory BP as compared with weak room heating resulting in a 10°C lower target room temperature when sufficient clothing and bedclothes are available. Methods: We conducted a parallel group, assessor blinded, simple randomised controlled study with 1:1 allocation among 146 healthy participants in Japan from November 2009 to March 2010. Ambulatory BP was measured while the participants stayed in single experimental rooms from 21:00 to 8:00. During the session, participants could adjust the amount of clothing and bedclothes as required. Compared with the weak room heating group (mean temperature±SD: 13.9±3.3°C), systolic morning BP (mean BP 2 h after getting out of bed) of the intensive room heating group (24.2±1.7°C) was significantly lower by 5.8 mm Hg (95% CI 2.4 to 9.3). Sleep-trough morning BP surges (morning BP minus lowest night-time BP) in the intensive room heating group were significantly suppressed to about two thirds of the values in the weak room heating group (14.3 vs 21.9 mm Hg; p<0.01). Conclusions: Intensive room heating decreased morning BP and the morning BP surge in winter.